The poetics of the riddle in Lesya Ukrainka`s "northern" works - Tymchenko, Antonina (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article considers the ways of realization of the motif of the riddle in the works by Lesya Ukrainka such as the poem "One word" and the fantasy "Polar Night". The artistic means of creating a mystery are analyzed at the level of metrics, syntax, vocabulary, phonics as well as at the semantic level. Lesya Ukrainka's lyrical heritage is rich in images of exotic loci, an interesting attempt was taken to recreate the topos of the north as a place inherently alien to the Ukrainians both psychologically (opposition "warm-cold", "near-far", "day-night") and socio-historically (the north as a place of exile of the intelligentsia, a point of no return, a hostile wasteland, which took away strength, health, deprived of life). In the poem "One Word" the author not only outlines this locus, but also speaks on behalf of its inhabitant. Recitative manner, folklore formulae introduce a fairy-tale context to the reader, syntactic constructions emphasize the mysterious context of the story. The phonics of the poem also gives the key to understanding the work: if at the beginning of the poem, which tells about the appearance of "strangers" in the settlement, close sounds of high rise like "y", "i" prevail, later we can see that rounded, "harmonious" "o" often appears to characterize the "stranger". Lesya Ukrainka is concluded to be a genius in mastering the word: the author subtextually emphasizes that, having a phantom freedom, a man dies because of the restriction of his freedom, existential inability to reach it neither at home nor in prison. In the fantasy "Polar Night" a phantasmagoric depiction of the meeting of an old man, a young fellow, a woman, a child in a mysterious locus, their conversation about darkness and light, day and night, the motives of the feast and spilled wine reflect the biblical context of the afterlife or the level of existential search for human existence, ability or inability to experience the joy, to wake up to a new life. All things considered, in the poetic works of Lesya Ukrainka there are still many unsolved mysteries, finding the key to which will allow us to read the hidden meanings of modern culture of the turn of XIX and XX centuries.